Nonhistone proteins HMG1 and HMG2 unwind DNA double helix. - Javaherian, K (1979)
In a previous communication we have shown that both HMG1 and HMG2 nonhistone proteins change the DNA helical structure and the binding of HMG1 and HMG2 to DNA induces a net unwinding equivalent of DNA double helix (Javaherian, K., Liu, L. F. and Wang, J. C. (1978) Science, 199, 1345-1346). Employing melting absorption technique, we now show that in the presence of salt HMG1 and HMG2 destabilize DNA whereas in the absence of salt, they both stabilize DNA molecules. Consequently the folded structure of HMG must play an important role in melting DNA. Furthermore, by measuring topological winding number using competition unwinding experiments, we conclude that HMG1 has a higher affinity for a single-stranded DNA relative to double-stranded DNA. These results together suggest that HMG1 and HMG2 unwind DNA double helix by local denaturation of the DNA base pairs. The net unwinding angles have been measured to be 22 degrees and 26 degrees per molecule of HMG1 and HMG2 respectively.